Identification of Single-Nucleotide Polymorphism, Linkage Disequilibrium, and Restriction Enzyme Analysis of the Growth Hormone Gene in Kampung Super Chicken - Sari, Apriliana Putri Zahara Nafsina Luvita; Maharani, Dyah; Febrianto, Firman; Maulana, Yasin Pradana; Tribudi, Yuli Arif (Program Studi Peternakan Fakultas Sains dan Teknologi Universitas Muhammadiyah Sinjai, 2025)
This study aimed to investigate single-nucleotide polymorphisms (SNPs) and haplotype diversity within the growth hormone (GH) gene of Kampung Super chickens, a hybrid breed derived from KUB males and commercial layer hens. In this study, thirty-eight blood samples of Kampung Super chicken were collected and analyzed. A total of 11 SNPs were identified within intronic regions of the GH gene. Despite their non-coding location, these variants may influence gene regulation through mechanisms such as alternative splicing, mRNA transport, or chromatin accessibility. Linkage disequilibrium (LD) analysis revealed several strong associations among SNP pairs, indicating the presence of conserved haplotype blocks potentially under stabilizing selection. In silico restriction enzyme analysis showed that five SNPs displayed three genotypic classes, and four of them could be effectively genotyped using PCR-RFLP, while one SNP (g.3018G/A) lacked suitable restriction sites. The SNP g.3094C/T exhibited high diagnostic potential using multiple enzymes (StuI, MspI, XmaI), while g.3129A/T was distinguishable using TaqI, although the adjacent SNP overlap limited interpretability. Two SNPs (g.3261C/T and g.3268G/A) were digestible by enzymes with multiple cut sites, complicating gel-based resolution. These findings provide a foundation for future functional and association studies and support the use of GH gene polymorphisms in marker-assisted selection strategies for growth-related traits in Kampung Super chicken.